Explikation personaler Leistungsvoraussetzungen in den neuen olympischen Canadier-Disziplinen der Frauen - Clauß, M.; Herrmann, H.; Hartmann, U. (Leipziger Sportwissenschaftliche Beiträge, 2017)
In the literature, it is assumed that the central-nervous fatigue is detectable on the basis of the haemodynamic response as an indicator (predictor) for neuronal activity. Whether for large-engine cyclic movements under the aspect of the load - Cohen (1997) and Friston et al. (1995), the model function of the hemodynamic response remains valid, - a predictive modeling of functional near-infrared spectroscopy (fNIRS) signals can be useful to estimate the model efficiency added to the regressor oxygen uptake or - The fNIRS is not suitable for determining neuronal activity is to be pursued in 2 pilot studies in Canadier women of canoe racing.